Alternaria leaf blight (Alternaria spp.) – an emerging foliar fungal disease of winter-summer groundnut (Arachis hypogaea) : A review - KUMAR, NARENDRA; DUTTA, RAM; AJAY, B C; RADHAKRISHNAN, T (The Indian Journal of Agricultural Sciences, 2022)
Alternaria leaf blight of groundnut (Arachis hypogaea L.) is an economic important foliar fungal disease of winter (rabi)-summer groundnut. It is not only distributed in India, but also in other groundnut growing countries like Nigeria, Vietnam and Thailand. Its severity increases whenever the crop is facing any biotic and abiotic stresses. This disease significantly affects pod and haulm yield of groundnut causing a reduction in the pod (13–22%), haulm yield (24–63%) and kernel quality. In cultivated groundnut, very limited sources of moderate resistance are available to Alternaria leaf blight. Now efforts are being made to identify better and stable sources of resistance in cultivated groundnut germplasm and interspecific derivatives. Although cultural, biological and chemical control measures have been used for the management of Alternaria leaf blight but these involve high costs and time. Growing Alternaria leaf blight resistant cultivars is the most effective way to protect groundnut crop. However, conventional breeding approaches have been successful for developing moderate resistance groundnut varieties for Alternaria leaf blight. This review has made an attempt to consolidate the research developments in Alternaria leaf blight and resistance breeding in groundnut.